The Principle of Legality in the Law of Misdemeanors and Violation the Measures Taken Due To Covid-19 - Berrin Akbulut (Ceza Hukuku ve Kriminoloji Dergisi)
Although the principle of legality is included in national and international texts, it is difficult to necessarily reconcile the compliance of regulations with the principle of legality, and problems are experienced in practice. The principle of legality in misdemeanors is regulated in Article 4 of the Code on Misdemeanors, and the same problems are also experienced over this issue. In the Code of Misdemeanors (Art. 4), giving authority to the administration in completing the content of the framework provision, the method preferred in the regulation of the framework provision, and the implementation of the regulations that restrict the fundamental rights and freedom by the regulatory process of the administration create problems in terms of practice and doctrine. Measures made necessary in Turkey and the wider world because of the pandemic have instigated the current debate on legality. Thus, the subject of the study has been determined as the principle of legality in the Code on Misdemeanors and violation of the measures taken due to COVID-19.